Effects of dual-career and marital conflict on the mental health of couples - Tam Cai Lian (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
The main purpose of this present article is to examine the effects of dual-career family and marital conflict on the general health of couples in Malaysia. Since marital conflict has been proven to predict health outcomes in couples, this study aims to find out how an individual’s conflict tactics has an impact on their spouse’s reaction. Besides, as the number of women entering the work force continues to rise, there is a need for us to find out the health effects of dual-career family. A random sample of 399 participants from Selangor who were either married or cohabitating were used in this study. Characteristics of conflict tactics in relation to general health were assessed and it was found that the results were significant though there is a low correlation between the two variables. However, results supported the hypothesis that how an individual handles conflict may have a positive influence on spouse’s ability to handle conflict. Significant relationship also exists between self-image with general health and also career salience with general health. This means that a person with a better sense of self and a promising career is more likely to have a better mental health